(untitled) (International Journal of Current Engineering and Technology, 2015)
LEDs provide effective lighting solutions. Their main advantages are efficiency, reliability and durability. Although LEDs operate cooler than conventional incandescent bulbs, it is necessary to achieve maximum heat transfer in order to maintain or improve their efficiency and lifespan. Heat sinks in LED modules provide a path for heat to flow from the source to the outside medium. Heat sinks with different fin geometries are analyzed to determine its influence on thermal performance and airflow around the fins. This adds options to the manufacturing field which is also of great importance. The thermal performance determines the effectiveness of different fin geometries for heat sinks to be used in LED lighting modules.